Пісня в житті та творчості Осипа Маковея - Жеплинський, Р. (Народна творчість та етнографія, 2007)
This article is dedicated to the role of song in life and creative activity of Osyp Makovey. The article is focused on his works which were set to music, and songs which Osyp Makovey collected and adapted.